DETERMINATION OF SALT TRANSFER PARAMETERS IN LYSIMETRIC STUDIES - Avlakulov, Meyli (Innovatsion texnologiyalar, 2024)
One of the main tasks of salt transfer research is the selection of a mathematical model that corresponds to given conditions based on the study of the structural features of individual horizons of the studied rock strata, the patterns of movement of substances, and methods for describing the action of these processes. This article examined some issues of modeling salt transfer under conditions of furrow irrigation of cotton, when seasonal deviations from the general direction of the process can be neglected. A method has been developed for determining the parameters of salt transfer under conditions of a stationary salt regime of soils in the aeration zone based on the average salinity of soils of a given thickness, during furrow irrigation of cotton, according to the data of lysimetric experiments. It is known that stationary ion-salt and water regimes are formed during long-term irrigation or under natural conditions and occur when the factors that contribute to the removal of salts from the rocks of the aeration zone and groundwater and the influx of salts are in equilibrium. The proposed method for determining the parameters of salt transfer under conditions of a stationary water-salt regime of soils, according to data from both field and laboratory experiments, takes into account the above-mentioned features. With a stationary distribution of salts and a constant speed of moisture movement in the soil aeration zone, the solution of the direct problem makes it possible to predict the average mineralization of pore solutions in the rocks of the aeration zone during furrow irrigation of cotton.